Weaving public health and safety nets to respond the COVID-19 pandemic - Fan, Di (Saf Sci, 2021)
How do governments take strategic actions in weaving public health and safety nets to respond to the COVID-19 pandemic? Embracing Moore’s strategic action framework, this study investigates how municipal governments can configure authorizing environment—operational capacity—public value attributes to weave public health and safety nets, in order to prevent and control the public health and safety emergency. Leveraging fuzzy-set Qualitative Comparative Analysis (fsQCA) with a sample of 323 Chinese cities, we identify a distinctive taxonomy of four equally effective configurations of urban actions in blocking COVID-19 transmission: social reassurance, proactive defence, decisive resiliency, and strengthened coercion. Overall, this study provides a novel insight of public health and safety management into battles against COVID-19 in human society.